Educación tecnología y cultura: propuesta de investigación exploratoria - Jorge A. González (Estudios sobre las Culturas Contemporáneas)
Brief report of a multi-method study in which the relationship between education, culture and technology is analyzed in educational settings as a sort of technologically mediated cultural practice. The intersection of three main vectors: cognition, technology and society is at the center of the proposal. The information is currently being gathered in seven Mexican cities through ethnographic observation, techno-biographies and discussion groups.